Challenges of foot self-care in older people: a qualitative focus-group study - Miikkola Maija; Lantta Tella; Suhonen Riitta; Stolt Minna (My University, 2022)
Background
Foot health is an important aspect of general health, and it can be maintained and promoted through foot self-care. However, little is known about older people’s experiences of caring for their feet. The aim of this study was to gather knowledge about experiences of foot self-care from the perspective of healthy older people in order to improve their welfare and their management of foot health.
Methods
A qualitative descriptive design with focus groups was used. Seventeen older people recruited from daytime activity centres participated in the focus groups (n = 4). The data were analysed using inductive content analysis.
Results
The participants described their foot self-care as including various activities, but they were hindered by the following factors: physical (e.g. changes in nail structure), external (e.g. seeking help from multi-level professionals) and internal (e.g. related to ageing). Foot self-care was considered to be important, but it was not systematically carried out. The participants thought that health-care professionals neglected patients’ feet.
Conclusions
Older people use a variety of methods to care for their feet. However, several factors hinder their ability to do so. Older people need advice, education and support to maintain their foot health. Future research is needed to identify effective ways to support older people in foot self-care and improve their welfare as active citizens.